Musik Sebagai Media Komunikasi Ekspresi Cinta (Analisis Semiotika Lirik Lagu “Rumah ke Rumah” Karya Hindia) - Cahya, Serafina Iubikrea Arsegi; Sukendro, Gregorius Genep (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
The development of musik that is increasingly advanced in the current era of globalization can no longer be avoided, the influence on the emergence of various types of songs. Even today's human activities are most often accompanied by musik, therefore it cannot be denied that humans and musik are related. Musik is one of the means that can be used by every individual to convey messages, which have a function to express themselves. Starting from the idea of expressing feelings, inner content, thoughts, opinions, and imagination. This study aims to understand that the song